Molecular Epidemiological Investigation of Plasmodium knowlesi in Humans and Macaques in Singapore - Wong, Pei Sze Jeslyn; Tan, Cheong Huat; Lee, Vernon; Li, Mei Zhi Irene; Lee, Kim Sung; Lee, Piao Jarrod; Balbir, Singh; Ng, Lee Ching (Mary Ann Liebert, Inc., 2011)
Singapore reported its first locally acquired human Plasmodium knowlesi infection in 2007, involving a soldier who had undergone training in a forested area where long-tailed macaques are frequently seen. Comprehensive disease surveillance and monitoring system that was set up after the initial case detected four additional human P. knowlesi cases in 2007 and one in 2008. All involved military personnel who had undergone training in the forested area, and none had traveled out of Singapore 1 month before the onset of symptoms. Screening for malaria parasites on blood obtained from long-tailed macaques revealed that wild monkeys (n¼3) caught from the forested area were infected with P. knowlesi, whereas peri-domestic monkeys (n¼10) caught from a nature reserve park were not infected with any malaria parasites. Phylogenetic analysis of the nonrepeat region of the P. knowlesi csp genes showed that the sequences obtained from the human cases were not distinct from those obtained from wild monkeys. Further, certain genotypes were shared between samples from humans and macaques. Our findings provide evidence that long-tailed macaques are the natural hosts of P. knowlesi in Singapore and the human cases acquired their infection in the same vicinity where these monkeys are found. Further, the risk of acquiring P. knowlesi infection among the general population of Singapore is small as evident from the absence of P. knowlesi in peri-domestic monkeys.